Analyzing The Role Of Instagram As A Digital Branding And Engagement Tool In Study Program Official Accounts (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Social media offers strategic opportunities for academic branding, yet many program-level accounts remain underutilized. This study analyzes the official Instagram account of the Digital Business Study Program at UPN Veteran Jawa Timur to assess content strategies, audience interactions, and engagement effectiveness. Using a qualitative descriptive case study approach, data were collected through content analysis, Instagram Insights, and semi-structured interviews. Results show a broad reach of 83.9% from non-followers, but engagement is largely passive, dominated by likes (94.4%) with minimal comments, shares, or saves. Achievement- and event-based content performed best, while stories and reels were underused, limiting interactive potential. SWOT analysis revealed strengths in visibility and credibility, weaknesses in engagement and retention, and opportunities in content diversification. Recommended strategies include optimizing non-follower conversion, enhancing interactive content, and leveraging achievement-based storytelling. The study demonstrates how program-level Instagram accounts can evolve from passive channels into strategic tools for visibility, engagement, and credibility in higher education.
Keywords: Instagram; digital branding; social media engagement; Higher Education; Audience Interaction